Contribution of Remittance in Poverty Alleviation - Paudel, Tej Prasad (Economic Review of Nepal, 2019)
Many Nepalese people used to go to foreign country to earn money. They send money to family member as remittance. Nowadays remittance become has one of the major sources of lively hood. Foreign Employment has become a major issue in the current economic and political discussion of Nepal. Another most important issue is the poverty alleviation from foreign employment remittance. The objective of this article is to describe the situation of poverty and analyze the contribution of remittance in poverty alleviation of Nepal. This study has been based on secondary data published by the Nepal government and covering a period between fiscal year 2011/12 to 2019/2020. The methodology to meet the objectives of this study is analytical and descriptive research design and writing style is also based on Publication Manual of American Psychological Association (7th ed.) This study shows the following findings During the study period, remittance was in increasing order and poverty is in decreasing order from FY 2011/12 to 2019/20.